Politik Kebangsaan Nahdlatul Ulama Perspektif Pemikiran KH. Abdul Muchith Muzadi - Rofi’i, Ahmad (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article discusses the KH. Abdul Muchith Muzadiâs point of view on Nahdlatul Ulama and the national political of NU. NU as a religious organizations based on the theory of Ahl wal Jamaah, having tenets include: tawassut (moderate), tawazun, tasamuh, and commanding the good and forbidding the evil; which has always been the political basis of nationality NU in Indonesian politics. In KH. Abdul Muchith Muzadiâs idea, nationality politics is defined as our responsibility in maintaining the integrity of the Unitary Republic of Indonesia (NKRI) is universally from groups separastisme that lead to disunity, disintegration and destruction, in the commitments, namely Pancasila. So, national politics of NU in the perspective of KH Muchith Muzadi is the appreciation of the national consensus and the embodiment of devotion NU in upholding the Unitary Republic of Indonesia (NKRI) as something that was final.Â Keywords: Politics, nationality, NU, and Abdul Muchith Muzadi